Turbine rotor blade erosion control with film cooling - Al-Hassani, T. S. J. (Cranfield University, 1982)
Component erosion in gas turbines can be a serious problem. The erosive particles which may be sand, ingested into compressors in desert regions, or carbon shed from gas turbine combustors, contribute to significant blade life reduction. In extreme cases, both sand and carbon particles can cause surface build up on turbine blades reducing efficiency and block the small diameter cooling holes thereby reducing cooling effectiveness. A two-dimensional turbine cascade tunnel was designed and built incorporating perspex rotor blades which were eroded for a variety of parametric conditions. The aerodynamic performance of the turbine cascade tunnel is examined with respect to pressure losses and efficiency. The introduction of film cooling air in varying quantities and configurations in the leading edge region is shown to significantly reduce erosive wear. Maximum erosion was found to occur close to the stagnation point on the suction surface of the aerofoils. The test Reynolds number and particle trajectories were chosen to closely represent the entry conditions of an actual film cooled turbine which had experienced this type of erosive wear in operation.